Новые виды диплозоид рода Paradiplozoon (Monogenea, Diplozoidae) - Хотеновский, И.А. (Вестник зоологии, 1982)
New species of the genus Paradiplozoon were found in collections of the Zoological Institute, USSR Academy of Sciences (Leningrad). P. vietnamicum sp. n. (Viet Nam fauna) differs from other vietnamese species, P. doi (Ha Ki) by smaller clamps and their structural peculiarities. P. megalobramae sp. n, (Amus-Chinase fauna) - differs from related species P. marinae (Achmerov) and P. parabramisi (Achmerov) by clamp structure. P. cyprini sp. n. (Amur-Chinese fauna) differs from other species of the fauna by clamp structure and folding of the body caudal part. P. tisae sp. n. (Palearctic fauna) differs from similar P. homoion (Bychowsky etNagibina)by fold number, medial hooks size and clamp structure; from P. leucisci sp. n., P. zeller ( G y n t o v t ) and P. al- burni sp. n. it differs by smaller, as compared to succers, pharynx size. P. leucisci sp. n. (Palearctic fauna) differs from P .homoion (Bychowsky et Nagibina) and siae sp. n. b y larger, as compared to succers, pharynx s i z eand clamp structure. P. alburni sp. n. (Palearctic fauna) differs from P. zeller ( G y n t o v t ) by fold number, medial hooks size and clamp structure.